Static Behavior of Circular Section CFRP Concrete-Filled Steel Tubes Under Compressive–Torsional Load - Wang, Qing-li; Zhao, Jie; Peng, Kuan (Frontiers in Materials, 2022)
In order to study the compressive torsional behavior of concrete-filled CFRP steel tubes (CF-CFRP-STs), the static test of eight circular section CF-CFRP-ST compression torsional specimens was carried out. The characteristics of the torque–angle (T–θ) curve and shear stress shear–strain (τ–γ) curve, failure mode, cooperative work between steel tubes and CFRP, and cross-section assumption were studied. The T–θ curve, τ–γ curve, and failure mode of the specimen are simulated by ABAQUS. Based on the above research, the stress distribution of each component material is analyzed. The effects of transverse CFRP layers, material strength, steel ratio, and axial compression ratio on the static performance of members are discussed. Based on the performance analysis, the bearing capacity equation of CF-CFRP-ST compression-torsional members is proposed.